Rahner’s Contribution to the Renewal of Sacramentology - Leijssen, Lambert (Philosophy & theology, 1995)
The essay reviews the evolution of Rahner’s understanding of sacrament and evaluates his contribution to the renewal of sacramentology. By elaborating the notion of the Church as basic sacrament of the world and by doing so in light of the theology of the Word, Rahner rescued sacramentology from the discussion of dead-end controversies about the number of sacraments and about the institution of the Church by Christ. This has provided the basis for a most promising model of sacrament for the ecumenical project.